Engels, Trotsky and the Natural Sciences: A case study in cosmology - Steinberg, Alex (Aurora. Revista de Arte, Mídia e Política, 2020)
The topic of this essay is Trotsky’s attitude to dialectical philosophy and the natural sciences. We will first summarize the tradition whose mantle Trotsky inherited as it was developed by Engels. We will then consider Trotsky’s relationship to the natural sciences. Trotsky, echoing Engels proclamations decades earlier, maintained that a dialectical philosophy is an essential guide to the work of the scientist while at the same time granting the autonomy and freedom of scientists to pursue their research. Trotsky had a lifelong interest in following the developments in the natural sciences. He also had an intuitive grasp of some important developments in the natural sciences that would only come to fruition decades after his death. We will then present a case study of how a dialectical approach to nature can assist in overcoming a crisis that is plaguing contemporary physics. Specifically we will discuss how a dialectical approach to nature can inform cosmology in the 21st century and avoid the philosophical pitfalls and dead-ends that mark the contemporary crisis in physics.